2011
DOI: 10.1186/1743-422x-8-292
|View full text |Cite|
|
Sign up to set email alerts
|

Effective inhibition of foot-and-mouth disease virus (FMDV) replication in vitro by vector-delivered microRNAs targeting the 3D gene

Abstract: BackgroundFoot-and-mouth disease virus (FMDV) causes an economically important and highly contagious disease of cloven-hoofed animals. RNAi triggered by small RNA molecules, including siRNAs and miRNAs, offers a new approach for controlling viral infections. There is no report available for FMDV inhibition by vector-delivered miRNA, although miRNA is believed to have more potential than siRNA. In this study, the inhibitory effects of vector-delivered miRNAs targeting the 3D gene on FMDV replication were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 36 publications
1
29
0
Order By: Relevance
“…Each miRNA expression plasmid (including pmiR-NC, the negative control; Table 1) was, with each reporter plasmid (including p3D-GFP, a control for nonspecific effects [41]), used to co-transfected BHK-21 cells at a molar ratio of 1:1 (w/w). The cells were observed continuously under the fluorescence microscope and analyzed by flow cytometry 48 h post-transfection.…”
Section: Resultsmentioning
confidence: 99%
“…Each miRNA expression plasmid (including pmiR-NC, the negative control; Table 1) was, with each reporter plasmid (including p3D-GFP, a control for nonspecific effects [41]), used to co-transfected BHK-21 cells at a molar ratio of 1:1 (w/w). The cells were observed continuously under the fluorescence microscope and analyzed by flow cytometry 48 h post-transfection.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also provided supportive proof of this conclusion. For instance, the results from Du et al [19] showed that vector-delivered miRNAs targeting the 3D genes efficiently inhibited the FMDV replication in vitro. Ahluwalia et al [20] found that human cellular miRNA hsa-miR-29a interfered with the expression of viral Nef protein and HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…As with shRNA, delivery of non-native miRNA constructs have been used to suppress target protein expression in cell cultures [4-6]. In whole animal models [30,31], pioneering studies in the cancer field have described impressive therapeutic effects with these non-native miRNAs, yet the approach had not been tested in heart, in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…With the recent developments in RNA interference technologies (RNAi), it is highly anticipated that these viral-based delivery approaches can be extended for the suppression of target protein expression in the heart [3]. The approach has been overwhelmingly successful in isolated cell culture models [4-6], including several studies for the suppression of malic enzyme as targeted in this study [7-9]. However, there are only a few reports for successful suppression of a target protein in heart, in vivo , based on RNAi schemes [10-14].…”
Section: Introductionmentioning
confidence: 99%